Strategic Innovative Marketing and Tourism Current Trends and Future Outlook$1 (B10th ICSIMAT, Ionian Islands, Greece, 2023 /s - Kavoura, Androniki; Borges-Tiago, Teresa; Tiago, Flavio; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
This open access book presents the latest findings of researchers from around the globe who presented their work at the 10th international conference of Strategic Innovative Marketing and Tourism (ICSIMAT) in 2023. It provides an up-to-date information and discusses current trends, issues, and debates, both theoretical and practical research, on strategic innovative marketing and tourism and applications from social media and emerging technologies in Artificial Intelligence and the Internet of Everything. Topics covered in the chapters include social media in marketing and tourism hospitality, culture, strategic tools, and techniques employed and implemented by some of the top research laboratories in the world to the industry. This book brings together work from both academia and industry and continues the successful impact of the previous years' conference on the academic discussion of the topics.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Tourism; Management; Marketing; Sustainability; Tourism Management; Marketing; Sustainability